TRADITIONAL ART PERFORMING BUILDING DESIGN IN MEDAN CITY WITH APROACH CONTEMPORARY ARCHITECTURE - Renita Indri Wulandari; Bhakti Alamsyah; Fitri Ramadhani (INFOKUM, 2022)
The City of Medan as a multicultural city which is a combination of several has many performing arts. So that with the things mentioned, it is used as an opportunity to create a diversity of attractions and cultural based tourist attractions. One form of support for this potential is a forum for realizing the diversity of performing arts. The design of this diverse performing arts space is then embodied in a performing arts building in the city of Medan .The design method used is to determine the flexibility othe f space indicator. The principthe le of flexibility of space that becomes the focus is the convertibility of space, The design of space is carried out through several indicators of Convertibility of space wvariablea variabel of Flexibilit o f space ,that is : (1) Orientation is a change in orientation and atmosphere with the wishes of the perpetrator without making a major overhaul of the existing space. (2) The proportion of multifunctional space adjusts several activities that are accommodated with various functions at different times